How successful have trade unions been? A utility-based indicator of union well-being - John H. Pencavel (Institute for the Study of Labor (IZA), 2008)
Can conventional economic analysis help in defining and measuring the success of labor unions? In this paper, a general indicator of union welfare is proposed and particular expressions for the wage and employment objectives of unions are rearranged to derive measures of union success or welfare. These indicators combine two measures: union density and the relative union-nonunion wage gap. The indicators are applied to describe the movement of union welfare in the United States over the past eighty years, the differences in union success among groups of U.S. workers, and the variation in union well-being across countries.
urn:nbn:de:101:1-20080828346
Keywords: J51; 330; Trade unions; union density; relative wage effect of unionism; union objectives; Gewerkschaft; Erfolgsfaktor; Nutzenfunktion; Gewerkschaftlicher Organisationsgrad; Lohndifferenzierung; USA